2011
DOI: 10.1111/j.1600-0781.2011.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different fluence rates on pain and clinical outcome in patients with actinic keratoses treated with photodynamic therapy

Abstract: According to our observations a fluence rate between 25 and 50 mW/cm2 is effective and better tolerated by patients treated with topical 5-ALA PDT for AKs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 24 publications
0
50
1
1
Order By: Relevance
“…It is not clear how far different red light sources result in different efficacy rates and pain scores. It has been reported that a higher fluence rate of the light source caused higher pain sensations [23]. However, in our study, the fluence rate (= irradiance, 196 mW/cm 2 ) of the broad-band VIS + wIRA light source, which caused significantly less pain during PDT but had comparable efficacy rates, was even higher than the irradiance with the incoherent halogen lamp (150 mW/cm 2 ).…”
Section: Discussioncontrasting
confidence: 70%
“…It is not clear how far different red light sources result in different efficacy rates and pain scores. It has been reported that a higher fluence rate of the light source caused higher pain sensations [23]. However, in our study, the fluence rate (= irradiance, 196 mW/cm 2 ) of the broad-band VIS + wIRA light source, which caused significantly less pain during PDT but had comparable efficacy rates, was even higher than the irradiance with the incoherent halogen lamp (150 mW/cm 2 ).…”
Section: Discussioncontrasting
confidence: 70%
“…The continuous 75 mW/cm 2 red light protocol was considered due to its standardized use across Europe while the choice of the fractionated 12.3 mW/cm 2 red light protocol was motivated by the FLEXITHERALIGHT Project (http://www.flexitheralight.com/). This French National Research Agency Project focuses on the development of a biophotonic device based on a flexible light emitting textile enabling a fractionated irradiation with a 12.3 mW/cm 2 fluence rate for the PDT treatment of actinic keratosis.…”
Section: Discussionmentioning
confidence: 99%
“…Dirschka et al [5] however, not only failed to discuss reasons for the differences between the narrow-band and broad-band types of sources used, but also did not comment on the differences found between the various types of broad-band sources employed. Additionally, despite the findings of von Felbert et al [2] who found the use of a broad-band source with water filter to be associated with less pain than that caused by a narrow-band source, and a study by Apalla et al [6] who found the use of a broad-band source without a water filter to be associated with pain, Dirschka and colleagues did not consider the fact that broad-band sources would result in absorption over a broader spectral range (and possibly encompassing several maxima) of the photosensitizer as has been discussed previously [7]. Additionally, previous studies in which no differences were found between narrow- and broad-band sources [1], [8], [9] were not considered.…”
Section: Lettermentioning
confidence: 98%
“…Possible reasons for such a pronounced difference between the response rates in these two studies were however not discussed by Dirschka and colleagues [5]. While the extent of pain experienced during photodynamic therapy (which is deemed to be the main side-effect of PDT [6], [7]) was documented by Dirschka et al [5], possible reasons for the greater incidence of pain during the use of the narrow-band sources were not considered. In the Dirschka et al study, a comparison of the photosensitizers used showed BF-200 ALA to be superior to MAL, but again, a study with contradictory findings (Gholam et al [3]) is not discussed.…”
Section: Lettermentioning
confidence: 99%